Sistem Informasi Akuntansi Penjualan dan Pembelian dalam Meningkatkan Pengendalian Internal (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The aim of this research is to find out how the sales and sales accounting information system is implemented in improving internal control. This research uses a qualitative type of research with primary data sources. The object of this research is PT. Mekar Dewatamali Jombang's work. The results of this research show that PT. Mekar Dewatamali Jombang's work in 2022 in improving the internal controls implemented and implemented has been progressing well. This is proven by the organizational structure which has carried out a strict separation of functions and responsibilities, an authorization system and recording procedures which provide sufficient level of protection for property. Healthy practices in carrying out the duties and functions of each organizational unit have been implemented by PT. The work of Miekar Diewatamali Jombang.